PENINGKATAN KEMAMPUAN SISWA KELAS VIII SMP NEGERI 1 LOEA DALAM MENULIS PUISI DENGAN TEKNIK MENULIS PUISI AKROSTIK - PAGEYASA, WAYAN (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
Write a poem as part of the creative writing is one of language skills must be learned by junior high school students in accordance with Education Unit Level Curriculum (KTSP). The goal is for students to express thoughts, feelings, and pengalamnnya with a beautiful and interesting language into poetic form. Reality encountered in the classroom students are still experiencing difficulties in learning to write poetry. he results showed that the use of TMPA can enhance students ability to write poetry, both at the stage of the discovery of ideas, writing, and presentation. Increasing students ability to write poetry at the discovery stage of the idea of looking at the sight of people exiting, seriousness, courage, creativity, and cooperation of students in performing each activity step. Increasing students ability to write poetry in the writing stage is shown with enthusiasm, perseverance, creativity, cooperation, and seriousness of the students in the process of developing ideas into poetry and poetry revision process is done individually, in pairs, and with feedback from teachers. Increased capacity at this stage is also seen in poetry written products of students. Students can develop ideas into poetry, may revise the poem based on the considerations and input from friends and teachers, and students can write the poem that has been revised. Increased ability to write poetry at the stage of presentation can be seen from the seriousness, courage, sight of people exiting, perseverance, and cooperation of students in the illustration, read poetry, display, and provides an assessment of the poems on display. In terms of products, students have experienced an increase in the illustration to the poem, read to the class, displaying a poem on the wall, and provide an assessment of poetry on display.Keywords: Improvement, ability, writing, poetry, acrostic